Sawkill Girls - Legrand, Claire, 1986- (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2018)
"From the New York Times bestselling author of Furyborn comes a breathtaking and spine-tingling novel about three teenage girls who face off against an insidious monster that preys upon young women ..."--From publisher website.